2019
DOI: 10.1080/00344893.2019.1643771
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Populist Local Democracy? The Consequences of Populist Radical Right Local Government Leadership in Western Europe

Abstract: A crisis of representation has precipitated a surge in support for populist radical right (PRR) parties that challenge the existing model of representative democracy. Simultaneously, institutional reforms across Western Europe have sought to improve the input legitimacy of local democracy with a proliferation of direct and participatory democratic methods. This paper investigates the extent to which PRR parties advance a populist democratic agenda when in leadership of the executive at the local level of gover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 88 publications
(54 reference statements)
0
8
0
1
Order By: Relevance
“…This article aims to fill the 'sub-national gap' by looking at the relationship between technocracy and populist discourse in the arena of urban governance in two local governments: Prague and Rome. To our knowledge, there have been very few attempts to explore empirically the role of populist politics in executive politics at the local level (Paxton 2019).…”
mentioning
confidence: 99%
“…This article aims to fill the 'sub-national gap' by looking at the relationship between technocracy and populist discourse in the arena of urban governance in two local governments: Prague and Rome. To our knowledge, there have been very few attempts to explore empirically the role of populist politics in executive politics at the local level (Paxton 2019).…”
mentioning
confidence: 99%
“…Second, future comparative studies could investigate the influence of institutional factors for the local mainstreaming strategies of populist radical right parties. Existing research shows the radicalism of these parties' pursuit of a populist democratic agenda varies according to the level of local government autonomy (Paxton 2019). Do populist radical right parties in countries with higher levels of subnational autonomy than France display greater independence from their central party office and implement more ideological policy?…”
Section: Discussionmentioning
confidence: 99%
“…The subnational arena has been assumed to be a location through which mainstreaming takes place, without investigation of the specific mechanisms (Akkerman et al 2016: 21;Kitschelt 2007Kitschelt : 1190. Crucially, in order to assess the radicalism of a local administration through its actions in office, recent studies have shown that partisan influence is also possible at this level of government (Paxton 2019;Weisskircher 2019). An analysis of the RN in local government therefore enables us to study a key PRR party that previously had next to no experience of government responsibility, in a context where it is also unconstrained by coalition dynamics.…”
Section: Moderation Of Radical Parties Through Democratic Participationmentioning
confidence: 99%
“…Second, the radical right accepts the essence of democracy in the name of 'the people,' albeit while opposing key elements of liberal democracies, i.e., minority rights, rule of law, and the separation of powers (Barney & Laycock, 1999). Further, radical-right leaders promote a 'plebiscitarian linkage' between the executive and 'the people,' which refers to the idea that they tend to act as the embodiment or more efficient executor of the general will of 'the people' once in government (Canovan, 2002, p. 34).This points towards the tension between the radical right's rhetoric of more direct participation and the actual democratic aspirations embodied therein (Canovan, 1999, p. 14;Paxton, 2019), essentially failing to grant citizens control over decision-making processes (Barney & Laycock, 1999). In practice, these opposing strands often overlap, rendering the participatory agenda of far-right actors profoundly ambiguous (Canovan, 2002, p. 34).…”
Section: The Ambiguous Participatory Agenda Of the Far Right And Its Mechanisms Of Contestationsmentioning
confidence: 99%